Kill yours, kill mine - Kovacic, Katherine (Poisoned Pen Press, 2024)
"Mia's grief counseling practice, The Pleiades, is named for the seven sisters from Greek mythology who were the companions of the Goddess of the Hunt-and in some stories, die of grief or are killed to be saved from attackers. Mia has been gathering broken women together for a radical form of group therapy. Amy. Gabrielle. Katy. Brooke. Olivia. Five women crippled with grief by the murders of their sisters--and seething with rage that the partners who killed them all walk free. She just needs one more. When Mia meets Naomi, she knows she has found the perfect candidate, but Naomi is resistant. She only needs to meet the others before she realizes that they, too, are consumed with desire for hands-on revenge. Under Mia's guidance, the women devise a plan to heal themselves. They'll take back their lives from the men who took their sisters. The premise is satisfyingly simple: I'll kill yours if you kill mine.."--